THE EFFECT OF EXCHANGE RATE, INFLATION, CAPITAL AND LABOR FORCE ON ECONOMIC GROWTH IN INDONESIA - Goya Kala; Raja Masbar; Sofyan Syahnur (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2018)
AbstractThe study aimed to analyze the influence of exchange rate, Inflation, capital and labor force on economic growth in Indonesia. The data in this study are secondary data sourced from the Central Bureau of Statistics and Bank Indonesia which include data on the rupiah exchange rate against the dollar, inflation, gross domestic fixed capital formation, and labor rate. Analysis of this research based on the Cobb-Douglas Production Function by using the ordinary least square method (OLS) recursively. The results showed that the capital positively affects economic growth. By recursive method, inflation and exchange rate have a significant effect on economic growth. Inflation in particular has a significant negative impact on economic growth through interest rates and capital. However, the amount of labor has no significant effect on economic growth. This means that the government needs to reduce the inflation rate to be able to reduce the interest rate to increase the amount of capital and ultimately increase economic growth in Indonesia.